Municipal model evaluation for providing drinking water and sanitation services in a developing country - Lugo, Kerlyn; Peraza, Yorman; Márquez, Adriana; Guevara, Edilberto; Pérez, Sergio; Buroz, Eduardo (Tecnología y ciencias del agua, 2025)
In this study, models for the provision of drinking water and sanitation services, were evaluated for the San Joaquin Municipality, Carabobo State, Venezuela, represented in the Municipal Autonomous Institute of Water of San Joaquin (IAGUASANJO, in Spanish) through three management indexes proposed in an integrated manner for drinking water and sanitation, a model index for the provision of drinking water services and model index for the provision of sanitation services. IAGUASANJO has oriented 65 % of the activities towards the provision of sanitation services and 35 % of the actions for the provision of the drinking water service in the period 2019-2023.